Simultation of the Effect of Land and Vegetation Management on Runoff and Sediment Yield From a Small Watershed- a case Study - Vinod Kumar P R (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 2000)
Conservation of soil by sound measures forms one of the fundamental premises towards a sustained future. The management of land and vegetation has profound influence in conservation programme. To simulate the effect of land and vegetation management measures on runoff and sediment yield from a waterhed, a study was conducted at Development Unit – IX of Attapadi region, in Palghat district. The relationship between effective rainfall and sediment mobilized due to rain storm was established as; ES = 28.57 ER0.9385., where ES is the effective sediment mobilized in T/km2 and ER is the effective rainfall in cm. The Universal Soil Loss Equation (USLE) was applied on perstorm basis to estimate the soil erosion. The Modified – USLE (R) factor was used to represent the erosivity factor in the soil loss estimation. The topographic factor (LS) was computed using the USLE and Revised – USLE methods. This particular parameter computed with the USLE was more than that of the RUSLE. The amount of soil erosion predicted with the USLE were more than that of the RUSLE due to greater LS factor associated with the USLE method. However both methods provided an ‘r2’ value of 0.9724. The WEPP – model was applied to simulate the runoff and soil erosion processes during individual rainstorm events. The model provided reliable simulation of the erosion process, but the runoff values were under – predicted for all the simulated events. The hillslopes cultivated with tuber crops gave maximum erosion per unit area during the simulation. The reason could be assumed as the absence of sufficient ground and canopy cover in this areas, which possessed a loosened surface after harvesting. The lands left as barren after tree felling also had increased rates of erosion during the simulation, which could be due to the lack of vegetative protection. While the paddy field had lesser rates of erosion owing to the flatness of land and vegetation cover. The other areas yielded reduced rates of erosion due to good canopy cover as well as surface cover provided by closely growing vegetation.